THE ROLE OF HALAL CERTIFICATION ON PURCHASE INTENTION TOWARDS FOOD PRODUCTS FROM MENA COUNTRIES: A SEM STUDY - Fanny Putera Perdana, Firdaus; Jan, Muhammad Tahir; Altunişik, Remzi; Jaswir, Irwandi; Kartika, Betania (Journal of Islamic Monetary Economics and Finance, 2019)
Kullu Halal (all Halal) is a concept that is highly applied in the Middle Eastern andNorth African (MENA) region as the majority of the population is Muslim. Manyproducts from non-Muslim countries are also exported to the MENA countries andsome of them are exposed to animal-based ingredients. Halal certification studies in theMENA region are found to be quite minimal to non-existent. The paper is designatedto analyze the effects of Halal certification towards the purchase intention of Muslimconsumers on food products from Muslim majority countries in the MENA countries.Theory of Planned Behavior (TPB) was used as a platform to predict the consumers’intention to purchase the Halal certified products. A self-administered questionnairewas selected as a method and the respondents are the Muslim consumers living incertain areas of Klang Valley, Malaysia. Five hundred questionnaires were distributed,and 417 questionnaires were considered usable. Structural Equation Modeling (SEM)was used as a method in this research. Attitude, Subjective Norm, and PerceivedBehavioral Control showed a strong correlation with Purchase Intention and the resultswere statistically significant at p < 0.05. Algeria was found to be the least trustworthycountry by the respondents, followed by Iran, Lebanon, Iraq, and Bahrain. The resultsindicate that the presence of Halal certification is important and will be profitable for thefood industry players in the MENA region. Despite being Muslim majority countries,it is important to ensure the presence of Halal certification in the products from MENAcountries, especially from those that received low scores in the country of origin study.